Strange Metal to Insulator Transition in Nanocrystalline SnO2. (2020) - Ahmad, Naseem; Khan, Shakeel; Ansari, Mohd Mohsin Nizam; Bhargava, Richa
Abstract: We have successfully studied the detailed electrical transport properties of SnO2 nanocrystallites. The tetragonal phase of the sample was confirmed by XRD measurement. The average crystallite size calculated from the Scherer equation and Williamson Hall analysis is found to be slightly different because of the strain effect in the crystal lattice. DC resistivity and dielectric properties have been studied for the material. DC resistivity measurement as a function of temperature depicts the metal to insulator transition in the sample that may be useful for resistive switching devices. The transition temperature for the as-synthesized sample is found to 353 K. Dielectric properties of the material were examined in the frequency range 42Hz-5MHz. Dielectric constant and dielectric loss tangent decrease and ac electrical conductivity increase with increasing frequency.